1958
DOI: 10.1042/bj0680114
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the amide and C-terminal residues in proteins. 3. The esterification of proteins

Abstract: The carboxyl groups of a protein can be esterified with diazomethane, but more conveniently with methanolic hydrochloric acid. In the present research, however, neither reagent has proved to be entirely satisfactory, for in our hands the first has not given full esterification and the second would do this only at the expense of the amide N, which we were particularly anxious to keep intact. Fraenkel-Conrat & Olcott (1945) were the first to show that the concentration of mineral acid (0-02 to 01 N) required to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

1959
1959
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 6 publications
3
43
0
Order By: Relevance
“…Native human albumin was prepared from plasma by the cold-ether fractionation technique of Kekwick & Mackay (1954). Chemically modified albumins were prepared by standard procedures as follows: esterification, by the method of Chibnall, Mangan & Rees (1958); acetylation, by the method of Marrack & Orlans (1954); bromoacetylation, by the method of Korman & Clarke (1956); phosphorylation, by the method of Ferrel, Olcott & Fraenkel-Conrat (1948).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Native human albumin was prepared from plasma by the cold-ether fractionation technique of Kekwick & Mackay (1954). Chemically modified albumins were prepared by standard procedures as follows: esterification, by the method of Chibnall, Mangan & Rees (1958); acetylation, by the method of Marrack & Orlans (1954); bromoacetylation, by the method of Korman & Clarke (1956); phosphorylation, by the method of Ferrel, Olcott & Fraenkel-Conrat (1948).…”
Section: Methodsmentioning
confidence: 99%
“…Amide groups were determined by the method of Chibnall et al (1958), and free amino groups by the method of Baddiley, Kekwick & Thain (1952). Methoxyl groups were measured by the Zeissel method (Grant, 1951) and phosphorus by the method of Allen (1940) after correction for inorganic orthophosphate (Lowry & Lopez, 1946 (2) albumin (2) pH 1-6 2-5 2-3 3-6 4-6 6-6 7-7 8-3 (Orgel, 1958).…”
Section: Methodsmentioning
confidence: 99%
“…The residue was dissolved in anhydrous trifluoroacetic acid (0.5 ml) and kept for 2 min at 20 "C. The A sample of CpCpA-Leu was hydrolysed with 0.2 M NaOH (5 min, 60 "C) and, after neutralization with 0.2 M acetic acid, the amount of leucine was estimated [28]. On the basis of a millimolar absorption coefficient of 28.1 for CpCpA a t 268 nm and pH 2, the ratio of CpCpA: Leu was found to be 1 .lo : 1 .oo.…”
Section: '5'-di-o-tetrahydropyranylcytidylyl-(3'+5')-adenosine ( I X )mentioning
confidence: 99%
“…It was found that significant degradation of the IgG was observed by SDS-polyacrylamide gel electrophoresis analysis, even at HCl concentrations as low as 0.05 M and at 25°C for 24 h. However, by employing a harsher procedure, i.e., performing the reaction for 48 h at the lower temperature of 4°C in the presence of 0.2 M HCl, degradation was no longer apparent by electrophoretic analyses, as shown in . The change in the mobility of the protein probably results from charge changes in the carboxyl functions of glutamic acid, aspartic acid, or C-terminal residues by methyl ester formation and methanolysis of the amide functions of glutamine and asparagine residues due to side reactions (21). Evidence from electrophoresis confirms that the integrity of the IgG molecule is maintained during the process of methyl esterification.…”
Section: Characterization Of Igg Methyl Estermentioning
confidence: 82%